The mechanism underlying transient weakness in myotonia congenita - Jessica H Myers; Kirsten Denman; Chris DuPont; Ahmed A Hawash; Kevin R Novak; Andrew Koesters; Manfred Grabner; Anamika Dayal; Andrew A Voss; Mark M Rich (eLife, 2021)
In addition to the hallmark muscle stiffness, patients with recessive myotonia congenita (Becker disease) experience debilitating bouts of transient weakness that remain poorly understood despite years of study. We performed intracellular recordings from muscle of both genetic and pharmacologic mouse models of Becker disease to identify the mechanism underlying transient weakness. Our recordings reveal transient depolarizations (plateau potentials) of the membrane potential to −25 to −35 mV in the genetic and pharmacologic models of Becker disease. Both Na+ and Ca2+ currents contribute to plateau potentials. Na+ persistent inward current (NaPIC) through NaV1.4 channels is the key trigger of plateau potentials and current through CaV1.1 Ca2+ channels contributes to the duration of the plateau. Inhibiting NaPIC with ranolazine prevents the development of plateau potentials and eliminates transient weakness in vivo. These data suggest that targeting NaPIC may be an effective treatment to prevent transient weakness in myotonia congenita.